2014
DOI: 10.2478/10004-1254-65-2014-2403
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of coarse and fine hand motor performance in asymptomatic subjects exposed to hand-arm vibration

Abstract: A frequently encountered exposure profile for hand-arm vibration in contemporary occupational setting comprises workers with a long history of intermittent exposure but without detectable signs of hand-arm vibration syndrome (HAVS). Yet, most of the published studies deal with developed HAVS cases, rarely discussing the biological processes that may be involved in degradation of manual dexterity and grip strength when it can be most beneficial -during the asymptomatic stage. In the present paper, a group of 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Prevalence figures around 42% have been reported by Cederlund et al 29 and up to 60%-80% by Sakakibara et al 30 Reduced manual dexterity has also been observed in vibration exposed asymptomatic workers. 31 Most of the exposed patients reported symptoms with tingling and numbness in hands and fingers. The opposite pattern was observed among the truck mechanics where few reported this kind of problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence figures around 42% have been reported by Cederlund et al 29 and up to 60%-80% by Sakakibara et al 30 Reduced manual dexterity has also been observed in vibration exposed asymptomatic workers. 31 Most of the exposed patients reported symptoms with tingling and numbness in hands and fingers. The opposite pattern was observed among the truck mechanics where few reported this kind of problem.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence figures around 42% have been reported by Cederlund et al 29 and up to 60%–80% by Sakakibara et al 30 Reduced manual dexterity has also been observed in vibration exposed asymptomatic workers. 31…”
Section: Discussionmentioning
confidence: 99%
“…People with the known HTR1B gene may be more susceptible to the development of secondary Raynauds’ phenomenon due to vibration exposure [ 33 , 34 , 35 , 36 ]. Prolonged vibration may reduce the manual dexterity [ 37 ]. Systemic adverse effects that result from local hand-arm vibration may include a cardiovascular response (echocardiographic changes (an increase in ejection fraction and stroke volume, enlarged left ventricular diastolic dimension, and reduction in heart rate) and lower blood pressure) [ 38 ], immunological changes (e.g., an increase in T cell lymphocytes of CD4 and CD8), and suppression of serum total cholesterol and triglyceride levels [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged vibration may reduce the manual dexterity [ 37 ]. Systemic adverse effects that result from local hand-arm vibration may include a cardiovascular response (echocardiographic changes (an increase in ejection fraction and stroke volume, enlarged left ventricular diastolic dimension, and reduction in heart rate) and lower blood pressure) [ 38 ], immunological changes (e.g., an increase in T cell lymphocytes of CD4 and CD8), and suppression of serum total cholesterol and triglyceride levels [ 36 , 37 , 38 ]. Vibration may promote vascular injury, endothelial injury, microvasculature changes [ 39 , 40 , 41 ], defects in vascular repair, and intravascular abnormalities (release of vasoactive mediators) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Im Vollbild der Erkrankung bestehen systemische Veränderungen (Zunahme alpha-2-adrenerge Rezeptoren, Transmitterpersistenz, Abnahme von alpha-1-adrenergen Rezeptoren) mit komplexen Dysfunktionen im zentralen und autonomen Nervensystem [11]. Die nervalen Schädigungen sind durch demyelinisierende Prozesse gekennzeichnet und betreffen die Thermozeption, Nozizeption sowie die Mechanozeption [14,15].…”
Section: Vibrationsbedingte Durchblutungsstörungenunclassified